Developing an algorithm for triad design - Abu Saa, Tareq M.; Ibrahim, Haslinda; Kalmoun, El Mostafa (Elsevier B.V., 2012)
The aim of this paper is to construct a method for developing a triad design on v objects TD(v), for the general case v=6n+1.This method depends on analyzing the triples to construct a starter for TD(v), denoted by STD(v), using interval techniques of the triples in the starter.We illustrate this construction by considering the cases v=13 and v=19 towards providing the design for the general case.